Basic Principles for the Implementation of Health Training (Lecture) - I. A. Vlasova (Acta Biomedica Scientifica, 2020)
Health of the population of the Russian Federation is an indicator of national safety. Therefore, one of the priority directions of state policy organization of events, providing preservation and increase in level of somatic health of citizens of the Russian Federation is considered. In this context, one of powerful methods of management of activity of the person is muscular work, long-term adaptation to which causes formation of a number of the effects having improving and preventive orientation. In this connection in recent years, the attention of experts and patients to the various systems of improving trainings increases, and the need for them in all of age groups of the population stimulates active development of their various forms and the fitness services industry. At the same time, achievement of necessary result demands understanding of both regularities of formation of adaptation reactions of an organism when using of the existing arsenal of physical activities, exercises, and the basic principles of their realization taking into account conclusions and recommendations of evidential medicine. These are organizational and methodical features of planning of training programs and styles of concrete occupations, the choice and dispensing both classical forms of physical activity, and options of technologies of fitness taking into account exercises potentially dangerous to the musculoskeletal device especially at children. Within the above-stated positions, the real material in a format of lecture statement is made and presented.